Prenatal stress and infant affective reactivity at five months of age - Rothenberger, Steffi Elena; Resch, Franz; Doszpod, Nora; Moehler, Eva (Early human development, 2011)
Background - Prospective studies concerning prenatal stress and its outcome on children's emotional development postulated a potential influence of prenatal hormonal levels or emotional stressors on child development [1-3]. In a retrospective study, an influence of maternal emotional stress on infant affective reactivity was found [4]. - Aims - This study was conducted in order to confirm these findings in a prospective study design. - Study design - A prospective longitudinal study design was conducted with three study waves during pregnancy and one time point five months postnatally. - Subjects - The final sample consisted of n=104 mother-infant dyads. - Outcome measures - Maternal baseline cortisol levels and emotional stress were assessed in each trimester of pregnancy. Children were examined with the infant reactivity battery according to Kagan & Snidman [5] at the age of five months. - Results - Mothers of children with high affective reactivity (cry score≥7) were significantly less depressed (p<.10) and perceived less stress (p<.05) in mid-pregnancy and were confronted with less external stress factors (p<.10) at the end of pregnancy. Cortisol levels did not differ in both groups in any pregnancy trimenon (p>.05). - Conclusions - These data add a new specific aspect to the ‘fetal programming hypothesis’ and are the first to confirm the speculative data from retrospective studies. Baseline cortisol does not seem to be the ‘hormonal mediator’ of this association. Therefore, cortisol stress reactivity or other neuroendocrine mechanisms should be assessed in future studies.